Study on Production of Microbial Lignolytic Enzymes for Deconstruction of Lignocellulosic Biomass for Feeding Ruminants: Current Trends and Future Prospects - Kumar, Vidya Pradeep; Sridhar, Manpal (Research Aspects in Agriculture and Veterinary Science Vol. 3, 2021)
Lignolytic enzymes such as laccase, manganese peroxidase, lignin peroxidase and versatile peroxidase secreted by ligninolytic fungi have been used to deconstruct lignocellulosic biomass for feeding ruminants. The article focuses on the analysis of ligninolytic enzymes and their applications with emphasis on the structures, catalysis, and reaction mechanisms. It also speaks about the fermentation methods employed for large scale production describing the analytical techniques used to assess the nutritive value of the feed in question. It does not emphasize on utilization of carbohydrate components of the crop residues for biofuel and generation of other renewable sources of energy from lignocellulosics. The objective is to provide an overall picture on the advantages of biological delignification of lignocellulosics for improved ruminant performance. The review portrays the current scenario of the ligninolytic enzyme technology and its relevance in livestock feed industry and scope for adapting the methods described for future interventions.